Pharmacokinetic and Pharmacodynamic Integration and Resistance Analysis of Tilmicosin Against Mycoplasma gallisepticum in an In Vitro Dynamic Model - Huang, Zilong; Wu, Yuzhi; Zhou, Zichong; Xia, Xirui; Gu, Xiaoyan; Cai, Qinren; Shen, Xiangguang; Yang, Hong; Ding, Huanzhong (Frontiers in Pharmacology, 2019)
Mycoplasma gallisepticum is the major pathogen causing chronic respiratory disease in chickens. In the present study, we successfully established a one-compartment open model with first order absorption to determine the relationship between tilmicosin pharmacokinetic and pharmacodynamic (PK/PD) indices and M. gallisepticum in in vitro. The aim was to simulate the PK/PD of tilmicosin against M. gallisepticum in lung tissues. And the results of static time-killing curves at constant drug concentrations [0-64 minimum inhibitory concentration (MIC)] showed that the amount of M. gallisepticum was reduced to the limit of detection after 36 h when the drug concentration exceeded 1 MIC, with a maximum kill rate of 0.53 h-1. In dynamic time-killing studies, tilmicosin produced a maximum antimycoplasmal effect of 6.38 Log10 CFU/mL reduction over 120 h. The area under the concentration-time curve over 24 h divided by the MIC (AUC24h/MIC) was the best PK/PD parameter to predict the antimicrobial activity of tilmicosin against M. gallisepticum (R2 = 0.87, compared with 0.49 for the cumulative time that the concentration exceeds the MIC (%T > MIC)). Therefore, tilmicosin showed concentration-dependent activity. Seven M. gallisepticum strains (M1–M7) with decreased susceptibility to tilmicosin were isolated from seven dose groups. These strains of M. gallisepticum had acquired resistance to erythromycin as well as to tylosin. No change in susceptibility to amikacin and doxycycline was observed in these strains. Gene mutation analysis was performed on the basis of annotated single nucleotide polymorphisms using the genome of strain S6 as the reference. For strain M5, a G495T mutation occurred in domain II of the 23S rrnA gene. In strain M3, resistance was associated with a T854A mutation in domain II of the 23S rrnB gene and a G2799A mutation in domain V of 23S rrnB. To the best of our knowledge, these tilmicosin resistance-associated mutations in M. gallisepticum have not been reported. In conclusion, tilmicosin shows excellent effectiveness and concentration-dependent characteristics against M. gallisepticum strain S6 in vitro. Additionally, these results will be used to provide a reference to design the optimal dosage regimen for tilmicosin in M. gallisepticum infection and to minimize the emergence of resistant bacteria.